PENGARUH KEBIJAKAN PERUSAHAAN DAN STRUKTUR KEPEMILIKAN TERHADAP NILAI PERUSAHAAN - Viveronica, Dwi Aldonna; Amanah, Lailatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThe primary objective of the company is to optimize the firm value, this research is aimed to examine the influence of firm policies and ownership structure to the firm value.This research is a quantitative research with the population is all manufacturing companies which are listed in Indonesia Stock Exchange in 2011-2015 periods. The selection of the research sample has been done by using purposive sampling method and seven companies which have metthe criteriawith 5 year research periods so the number of the observation is 35 observations. The analysis technique has been done by using multiple linear regression analysis and the SPSS 20.Based on the result of goodness of fit test the models which have been built have met the fit criteria. The result of the research indicates that (1) debt policy give negative influence to the firm value, (2) the investment policy give positive influence to the firm value, (3) dividend policy does not give any influence to the firm value, (4) institutional ownership give positive influenceto the firm value (5) managerial ownership does not give any influence to the firm value.Keywords: debt policy, investment policy, dividend policy, ownership structure.